La carpoteca del Herbario TEFH: una herramienta de apoyo en la educación e investigación - Ortega, Joel (2024)
The carpothecas are considered collections that houses dried fruits. The objective of this work is to document the collection storing large fruits that accompany the specimens deposited in the TEFH Herbarium collection. The fruits were curated, labeled, photographed, categorized by size and stored in paper bags; they are organized in a database. The fruit collection of the TEFH herbarium has a total of 224 dehiscent and indehiscent fruits, belonging to 35 families, of which 92 fruits correspond to the Pinaceae family, followed by Malvaceae (13), Fabaceae (12), Elaeocarpaceae (9), Meliaceae (9) and Apocynaceae (8) being the families with the highest number of species. This fruit collection plays a crucial role in the preservation and study of plant diversity and provides valuable information on the flora of Honduras as it includes material collected in coniferous and cloud forests.